The practical application of “Team-based learning” mode in fundamental medical courses: Medical Immunology as the example - Zhao, Xuerong; Ding, Shi; Wang, Jianping; Wang, Lingling; Mao, Shufang; Li, Yuhong; Xiao, Li Jun (Journal of the Pakistan Medical Association, 2026)
Objective: To systematically implement the team-based learning framework as a replicable model for curriculum innovation in foundational medical disciplines. Method: The educational intervention research study was conducted from March, 2021 to July, 2021 at Chengde Medical University after approval from the ethics review board of Chengde Medical University, China, and comprised Clinical Medicine students at the Department of Medical Immunology. The two groups had comparable baseline demographic and academic profiles. The intervention in group A was implemented over 15 consecutive academic weeks with 4 theoretical teaching hours per week. Theoretical instruction integrated case-driven inquiry, problem-based learning, role-reversal simulations, and seminar-style discourse. Practical training adopted a hierarchical structure, encompassing core laboratory experiments, elective investigative projects, and university-level innovation initiatives. Multimodal methodologies were utilised to optimise knowledge retention. Positive value of respecting life enriched case studies were embedded to integrate professional ethics and humanistic values, while a competency-centric evaluation system tracked team-based processes and individual skill progression. Those in group B received a conventional teacher-centred instructional model characterised by instructor-dominated didactic lectures, supplemented with regular homework assignments. Results: The two groups of students were comparable across all baseline characteristics (Table 1 for details). Post-intervention evaluations demonstrated overwhelmingly superior outcomes for the TBL approach. Satisfaction rates in the TBL group consistently exceeded 90% (reaching up to 99.4%) across theoretical and practical domains, significantly outperforming the LBL group (satisfaction rates: 52.8%-66.3%; all inter-group comparisons p < 0.001). Empirical outcomes demonstrated significant improvements in learners’ autonomous knowledge acquisition, collaborative problem-solving proficiency, translational research capabilities, and interdisciplinary innovation competencies. The team-based learning framework also fostered enhanced clinical reasoning and ethical awareness among the participants. Conclusion: The team-based learning paradigm was found to be a transformative pedagogical tool, providing a robust foundation for competency-driven medical education. Its scalable design offered actionable insights for curriculum reform across foundational medical and allied health disciplines, aligning with the evolving demands of global healthcare education. Key Words: Team-based learning, TBL, Medical immunology, Competency-based education, Translational research, Interdisciplinary innovation.